Population Dynamics of Dragonflies at The Paddy Field Ecosystem, Sidorejo, Central Bengkulu - Indriani, Gisela Ratna; Singkam, Abdul Rahman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
The rice fields of Sidorejo Village have the potential for dragonfly diversity. This study aims to analyze fluctuations in the diversity and abundance of dragonflies in three ecosystem conditions of rice fields in Sidorejo Village, Bengkulu Tengah. Sampling using purposive sampling with the cruising method. Data analysis was carried out descriptively through the identification of characteristics to obtain the name of the species. After the species name was obtained, the relative abundance, Shannon Wienner diversity index, and species evenness index were calculated. The results of the study found that the harvest ecosystem had the highest diversity and abundance of dragonflies (13 species and 45 individuals). The species that were consistently found in three types of ecosystems were Orthetrum sabina, O. testaceum, and Pantala flavescens. The species with the highest relative abundance was O. sabina with 32%. The diversity index ranged from 1.32 (post-harvest) to 2.25 (harvest). The highest evenness index was in the post-harvest ecosystem at 0.95, and the lowest was in the harvest ecosystem at 0.87. The results of this study are expected to show that the diversity and abundance of dragonflies fluctuate depending on seasonal ecosystem conditions in the rice fields.